Medical resident’s skill to communicate bad news - Guillén-López, Otto Barnaby (2019)
Breaking bad news is a clinical skill that every physician should possess. In this study, we seek the way in which the medical residents were communicating bad news in the hospital. Nineteen residents were surveyed in a public hospital in 2015. It was found that 100 % of residents had not received any training on the subject although all had given some bad news in the last month. Feelings of frustration in breaking bad news were found in 68,4 %. Besides, 53,3 % of the residents reported that there was not an adequate place to give bad news. It is concluded that breaking bad news is a frequent activity in medical professional practice but it is not generally taught.